The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/acel.13789
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional chromatin re‐organization during muscle stem cell aging

Abstract: Age‐related skeletal muscle atrophy or sarcopenia is a significant societal problem that is becoming amplified as the world's population continues to increase. The regeneration of damaged skeletal muscle is mediated by muscle stem cells, but in old age muscle stem cells become functionally attenuated. The molecular mechanisms that govern muscle stem cell aging encompass changes across multiple regulatory layers and are integrated by the three‐dimensional organization of the genome. To quantitatively understand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 132 publications
1
2
0
Order By: Relevance
“…We hypothesized that age-associated systemic inflammation might affect the epigenome and transcriptome of MuSCs. Following our results, we performed an in-depth examination of the aged MuSC transcriptome and found that one of the most significantly enriched pathways was “Chromatin organization” ( Figure 1F ), in with our initial hypothesis and previous reports 7 , 26 . Of particular interest was the lysine methyltransferase Kmt5a, because of its crucial role in maintaining H4K20 methylation.…”
Section: Resultssupporting
confidence: 84%
“…We hypothesized that age-associated systemic inflammation might affect the epigenome and transcriptome of MuSCs. Following our results, we performed an in-depth examination of the aged MuSC transcriptome and found that one of the most significantly enriched pathways was “Chromatin organization” ( Figure 1F ), in with our initial hypothesis and previous reports 7 , 26 . Of particular interest was the lysine methyltransferase Kmt5a, because of its crucial role in maintaining H4K20 methylation.…”
Section: Resultssupporting
confidence: 84%
“…We hypothesized that age-associated systemic in ammation might affect the epigenome and transcriptome of MuSCs. Following our results, we performed an in-depth examination of the aged MuSC transcriptome and found that one of the most signi cantly enriched pathways was "Chromatin organization" (Figure 1F), in with our initial hypothesis and previous reports 7,26 . Of particular interest was the lysine methyltransferase Kmt5a, because of its crucial role in maintaining H4K20 methylation.…”
Section: Age-associated Systemic In Ammation and Muscs Epigenetic Rem...supporting
confidence: 83%
“…Monocyte/macrophage infiltration exacerbates inflammation in liver, which is positively correlated with the progression of NAFLD [ 63 ]. Liver macrophages are characterized as IMs and resident Kupffer cells (KCs) based on their gene expression profiles and developmental origins [ [64] , [65] , [66] ]. In the literature, cell expression signature of CX3CR1 + has been used as a marker of IMs, and CX3CR1 - has been used as a marker of KCs [ 67 ].…”
Section: Resultsmentioning
confidence: 99%